Tergal and pleural structures contribute to the formation of ectopic prothoracic wings in cockroaches. Issue 8 (August 2016) - Elias-Neto, Moysés; Belles, Xavier
Abstract : Wings were a fundamental morphological innovation for the adaptive radiation of insects, the most diversified group among all animals. Pterygote insects have two pairs of wings, the mesothoracic (T2) forewings and the metathoracic (T3) hindwings, whereas the prothorax (T1) is wingless. Using RNA interference approaches, we have found that the gene Sex combs reduced ( Scr ) determines the wingless identity of T1 in the cockroach Blattella germanica . Interference of Scr triggers the formation of ectopic wing structures in T1, which are formed from the expansion of the latero-posterior region of the pronotum, along with a contribution of the epimeron, a pleurite of T1. These data support the theory of a dual origin for insect wings, from pronotal (tergal origin theory) and pleural (pleural origin theory) structures and genes.